EQUAL AI: A Framework for Enhancing Equity, Quality, Understanding and Accessibility in Liberal Arts through AI for Multilingual Learners - Davoodi, Amin (Language, Technology, and Social Media, 2024)
The integration of artificial intelligence (AI) into liberal arts education offers a transformative opportunity to address the diverse needs of multilingual and multicultural learners. Consequently, this study introduces the EQUAL AI framework (Enhancing Equity, Quality, Understanding, and Accessibility in Liberal Arts through AI), a structured approach to utilizing AI to foster inclusion and innovation in liberal arts pedagogy. The framework identifies five key domains: linguistic support, cultural representation, creative expression, critical thinking, and collaborative learning. Additionally, the study underscores the necessity of systemic support, particularly through professional development programs that equip educators with technical proficiency, ethical awareness, and the ability to critically assess AI tools. By tackling challenges such as algorithmic bias, data privacy, and the digital divide, the study advocates for culturally responsive policies and inclusive practices. The EQUAL AI framework envisions liberal arts education as a space for equitable participation and cultural understanding, positioning AI as a tool to enhance rather than replace humanistic pedagogy, ensuring its relevance in a technology-driven, interconnected world.